Bases Gaussianas Acuradas de Qualidade Sêxtupla Zeta para Elementos do Quarto Período e Aplicações em Moléculas - Ratuchne, Fernando (2014)
The development of basis set has been goal of very research groups. From this perspective, Pople developed compact basis set, which computational fast calculations, but with little accuracy. Dunning generated basis set which providing very accurate results, however, the computational cost associate the this basis set is high, even for today`s computing resources. These facts provide a window to the development of basis sets, which exhibit computational times lower than those for the sets of Dunning, and promoting results with same order of accuracy. For this purpose, the Generator Coordinate Hartree-Fock Polynomial Method (p-MCHF), is presented as a tool of the great power and effectiveness, promoting the attainment of compact and accurate basis set. In this study, have been generated basis set for representative elements fourth period, zinc and hydrogen, of quality sixfold zeta in the valence, using p-MCGHF. Sets generated were applied to molecules formed by the elements mentioned. The results were compared with sets of Dunning in calculations with various levels of theory (HF, B3LYP, B3PW91 and MP2). The accuracy is found above of the Dunning sets in hybrids and MP2 functional, with significantly lower computational costs. Studies of generators parameters of the basis sets p-MCGHF, Ωmin, ∆Ω and α, showed which they follow a linear tendency, the interpolation can be performed, avoiding the process of optimizing of the basis set, providing time savings in the developing process of the basis set, without loss of quallity.